Assessment of a decontamination process for hydrocyanic acid in linseed intended for use in animal feed. (4th October 2017) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hoogenboom, Laurentius (Ron); et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Contaminants in the Food Chain (CONTAM) provided a scientific opinion on the assessment of a decontamination process for the enzymatic treatment and subsequent heating of linseed, in order to reduce the amount of hydrocyanic acid (HCN) present as cyanogenic glycosides. Specifically, it is required that the feed decontamination process is compliant with the acceptability criteria specified in the Commission Regulation (EU) 2015/786 of 19 May 2015. With this aim, the CONTAM Panel assessed the data provided by the feed business operator with respect to the efficacy of the process to remove the contaminant from the linseed batches and on information demonstrating that the process does not adversely affect the characteristics and the nature of the product. The data enabled the Panel to conclude that in agreement with the literature the process was able to remove HCN by about 90%, and that it is possible to meet the current EU requirements for quality of linseed with respect to HCN, provided the level of contamination of untreated linseed would be within the range of the tested batches. The Panel noted that the amounts of other products formed during the enzymatic process and remaining in the treated material are not of toxicological concern. The experimental data provided by the feed business operator showed that the characteristics of linseed were not adversely affected by the decontamination process. The CONTAM Panel concluded that, on the basis of the information submitted by the feed business operator, the proposed decontamination process to remove HCN from linseed by means of enzymatic release and subsequent evaporation was compliant with the acceptability criteria provided for in Commission Regulation (EU) 2015/786 of 19 May 2015.